2010
DOI: 10.1371/journal.pone.0010373
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for STAT4 as a Common Autoimmune Gene: rs7574865 Is Associated with Colonic Crohn's Disease and Early Disease Onset

Abstract: BackgroundRecent studies demonstrated an association of STAT4 variants with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), indicating that multiple autoimmune diseases share common susceptibility genes. We therefore investigated the influence of STAT4 variants on the susceptibility and phenotype of inflammatory bowel diseases (IBD) in a large patient and control cohort.Methodology/Principal FindingsGenomic DNA from 2704 individuals of Caucasian origin including 857 patients with Crohn's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 56 publications
4
40
0
1
Order By: Relevance
“…One such study, conducted on more than 2,000 patients and replicated in a second cohort of almost 3,000 patients, identified as the strongest susceptibility locus (besides the HLA region) an SNP in the CD247 gene and confirmed the previously known association with STAT4 and IRF5 gene polymorphisms [11••]. Although they are potentially very interesting for gaining insight into the pathogenesis of SSc, genetic associations in the same loci have been found in other conditions, such as systemic lupus erythematosus (SLE) [12,13] and rheumatoid arthritis [14]. Therefore, detailed comparative studies are needed to assess their specificity for SSc.…”
Section: Genome-wide Association Studies For the Identification Of Gesupporting
confidence: 63%
“…One such study, conducted on more than 2,000 patients and replicated in a second cohort of almost 3,000 patients, identified as the strongest susceptibility locus (besides the HLA region) an SNP in the CD247 gene and confirmed the previously known association with STAT4 and IRF5 gene polymorphisms [11••]. Although they are potentially very interesting for gaining insight into the pathogenesis of SSc, genetic associations in the same loci have been found in other conditions, such as systemic lupus erythematosus (SLE) [12,13] and rheumatoid arthritis [14]. Therefore, detailed comparative studies are needed to assess their specificity for SSc.…”
Section: Genome-wide Association Studies For the Identification Of Gesupporting
confidence: 63%
“…Accordingly, patients with SLE show up-regulation of the type 1 IFN system [8]. Apart from this, STAT4 has also been reported to be associated with many other autoimmune diseases, such as rheumatoid arthritis, Crohn's disease, asthma, systemic sclerosis, and Sjögren's syndrome [9][10][11][12][13]. In the genetic analysis of SLE susceptibility, several genome-wide association studies (GWAS) have identified STAT4 as a susceptible gene.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, STAT4 haplotype characterized by the rs7574865 polymorphism was reported to be significantly associated with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and other autoimmune diseases such as Sjögren's syndrome, type 1 diabetes, and systemic sclerosis [16][17][18]. Interestingly, a recent casecontrol study conducted in a Spanish population showed that the T allele of the STAT4 rs7574865 was associated with IBD [19], and this association has been replicated by Diaz-Gallo et al [20] and Glas et al [21], they reported that rs7574865 polymorphism was associated with colonic CD and early disease onset in Caucasians. However, there are also some other studies did not confirm these findings.…”
Section: Introductionmentioning
confidence: 91%